Postharvest Application of 24-Epibrassinolide Reduces Chilling Injury Symptoms and Enhances Bioactive Compounds Content and Antioxidant Activity of Blood Orange Fruit - Habibi, Fariborz; Serrano, María; Zacarías, Lorenzo; Valero, Daniel; Guillén, Fabián (Frontiers in Plant Science, 2021)
Blood oranges (Citrus sinensis L. Osbeck cv. Sanguinello) fruit were treated with 24-epibrassinolide (Br) at 1, 5, and 10 µM previous to storage at 5 °C during 42 days. The samples were analysed after 14, 28, and 42 days plus 2 days at 20 °C. Chilling injury was reduced in Br-treated fruit based on the lower percentage of electrolyte leakage and visual symptoms of peel dehydration and browning. Treated fruit showed lower acidity losses, due to retention of the main organic acids’ concentration (citric and malic acids), as well as was higher content of sugars (sucrose, fructose, and glucose), especially in those fruit treated with the highest concentration (10 µM). Total phenolics and hydrophilic total antioxidant activity (H-TAA) decreased in control fruit over storage, while Br-treated fruit showed significantly higher concentration. In addition, total anthocyanins were enhanced in Br-treated oranges, which were correlated with colour Hue angle. Overall, the application of Br at 10 µM provides results increasing the storability of blood oranges and their content on bioactive compounds with antioxidant activity.